Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1016/j.ydbio.2008.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activation by GAGA factor is through its direct interaction with dmTAF3

Abstract: The GAGA factor (GAF), encoded by the Trithorax like gene (Trl) is a multifunctional protein involved in gene activation, Polycomb-dependent repression, chromatin remodeling and is a component of chromatin domain boundaries. Although first isolated as transcriptional activator of the Drosophila homeotic gene Ultrabithorax (Ubx), the molecular basis of this GAF activity is unknown. Here we show that dmTAF3 (also known as BIP2 and dTAF(II)155), a component of TFIID, interacts directly with GAF. We generated muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 62 publications
0
43
0
Order By: Relevance
“…GAGA factor might open up the chromatin structure by interacting with the chromatin remodeling factor nucleosome remodeling factor (NURF; Xiao et al 2001) and the histone chaperon, Facilitates Chromatin Transcription (FACT) (Nakayama et al 2007). GAGA factor has also recently been found to interact with a subunit of TFIID, thus allowing GAGA factor to facilitate preinitiation complex formation (Chopra et al 2008).…”
Section: Positioned Nucleosomes Might Contribute To Promoter Proximalmentioning
confidence: 99%
“…GAGA factor might open up the chromatin structure by interacting with the chromatin remodeling factor nucleosome remodeling factor (NURF; Xiao et al 2001) and the histone chaperon, Facilitates Chromatin Transcription (FACT) (Nakayama et al 2007). GAGA factor has also recently been found to interact with a subunit of TFIID, thus allowing GAGA factor to facilitate preinitiation complex formation (Chopra et al 2008).…”
Section: Positioned Nucleosomes Might Contribute To Promoter Proximalmentioning
confidence: 99%
“…10 A significant amount of data indicates that BTB domains are involved in the recruitment of non-BTB-containing regulator proteins. [11][12][13] Another set of experiments have shown that BTB domains of different proteins in some cases can specifically interact with each other, but it is unknown how such interactions proceed. Rarely, heterodimerization of two different BTBs has been observed.…”
Section: Introductionmentioning
confidence: 99%
“…A few BTB-zinc finger proteins, including Drosophila GAGA factor, also have the ability to activate transcription (Biggin and Tjian 1988;Staller et al 2001;Rodova et al 2004). Recently, the GAGA factor BTB domain was shown to bind to the TAFIID general transcription factor subunit TAF-3, suggesting that the GAGA factor may function as a transcriptional activator by recruiting the core TAFIID machinery to its target promoters (Chopra et al 2008). In general, 1 however, much less is known about protein interactions of the BTB domain in BTB-zinc finger proteins that function as activators.…”
mentioning
confidence: 99%